2022
DOI: 10.1101/2022.02.22.481530
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The phase of sensorimotor mu and beta oscillations has the opposite effect on corticospinal excitability

Abstract: Neural oscillations in the primary motor cortex (M1) shape corticospinal excitability. Power and phase of ongoing mu (8-13 Hz) and beta (14-30 Hz) activity may mediate motor cortical output. However, the functional dynamics of both mu and beta phase and power relationships and their interaction, are largely unknown. Here, we employ recently developed real-time targeting of the mu and beta rhythm, to apply phase-specific brain stimulation and probe motor corticospinal excitability non-invasively. For this, we … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 74 publications
(154 reference statements)
1
11
0
Order By: Relevance
“…Regarding the aftereffects of the µ-tACS paradigm on CSE, we observed significant increases in mean MEP amplitude from pre- to post-tACS for both the FDI (43.3% increase) and ADM (50% increase), in line with recent µ-tACS studies (Feurra et al, 2019; Fresnoza et al, 2018; Madsen et al, 2019a) and thus, supporting a facilitatory effect of µ oscillations on CSE (Bergmann et al, 2019; Karabanov et al, 2021; Ogata et al, 2019; Thies et al, 2018; Wischnewski et al, 2022). The response rate for this facilitatory effect was also relative;y consistent across participants, with 11 of the 13 participants demonstrating an increase in MEP amplitude (∼85% response rate), which represents, to our knowledge, the most effective means of increasing CSE across the multitude of plasticity-inducing paradigms currently in use (López-Alonso et al, 2014; Pellegrini et al, 2018; Veniero et al, 2015).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Regarding the aftereffects of the µ-tACS paradigm on CSE, we observed significant increases in mean MEP amplitude from pre- to post-tACS for both the FDI (43.3% increase) and ADM (50% increase), in line with recent µ-tACS studies (Feurra et al, 2019; Fresnoza et al, 2018; Madsen et al, 2019a) and thus, supporting a facilitatory effect of µ oscillations on CSE (Bergmann et al, 2019; Karabanov et al, 2021; Ogata et al, 2019; Thies et al, 2018; Wischnewski et al, 2022). The response rate for this facilitatory effect was also relative;y consistent across participants, with 11 of the 13 participants demonstrating an increase in MEP amplitude (∼85% response rate), which represents, to our knowledge, the most effective means of increasing CSE across the multitude of plasticity-inducing paradigms currently in use (López-Alonso et al, 2014; Pellegrini et al, 2018; Veniero et al, 2015).…”
Section: Resultssupporting
confidence: 89%
“…Mu (µ) oscillations (8–13 Hz) are one of the most prominent rhythms in the sensorimotor cortex during resting wake (Craddock et al, 2017; Hari, 2006; Weisz et al, 2014; Zhang and Ding, 2010) and are proposed to modulate CSE in a phase-specific manner (Baur et al, 2020; Berger et al, 2014; Bergmann et al, 2019; Hussain et al, 2018; Schaworonkow et al, 2018; Schaworonkow et al, 2019; Stefanou et al, 2018; Wischnewski et al, 2022; Zrenner et al, 2018;), with µ troughs thought to reflect active facilitation of gamma activity and information processing, referred to as the “pulsed facilitation” hypothesis (Bergmann et al, 2019). However, these troughs may instead reflect “pulsed inhibition” (akin to occipital alpha oscillations; Mathewson et al, 2011; Mazaheri and Jensen, 2010; Schalk, 2015) of the primary somatosensory cortex (S1) that results in a net transient local disinhibition of feed-forward inhibitory inputs from S1 to the primary motor cortex (M1; Bergmann et al, 2019; Murray and Keller, 2011; Thies et al, 2018; Turco et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, closed-loop neuromodulation studies, in which stimulation parameters are adapted to the dynamics of the brain in real-time, have exploited the phase of some oscillations to do just that. For example, closed-loop phase-locked TMS studies have shown that the magnitude of TMS-induced muscle-evoked-potentials is dependent on the instantaneous phase of the rhythms of the motor cortex, such as the mu and/or beta rhythms [22][23][24][25] . Similarly, transcranial alternating current stimulation (TACS) matching the frequency and phase of slow oscillations during sleep has been shown to enhance these oscillations and impact overnight memory consolidation 26 .…”
Section: Introductionmentioning
confidence: 99%
“…In human research, TMS physiological effects can be measured non-invasively through motorevoked potentials [5][6][7] , functional magnetic resonance imaging [8][9][10] , and electroencephalography (EEG) [11][12][13][14][15][16] . Combined TMS-EEG is a promising method to study neural population responses to TMS with high temporal accuracy.…”
Section: Introductionmentioning
confidence: 99%